Bioethics' Conceptual Tool Kit - Kaebnick, Gregory E. (The Hastings Center report, 2023)
Two articles in the March-April 2023 issue of the Hastings Center Report challenge principlism and propose new moral frameworks for bioethics. In the lead article, Tyler Tate and Joseph Clair argue that bioethics must be grounded in an understanding of ideal character and relationship to others. The virtue of love, they propose, provides the fundamental conceptual and emotional resources that physicians need. In the second article, Samuel Reis-Dennis offers historical and philosophical explorations of Kantian versus bioethical conceptions of autonomy as he argues that bioethics should be centered on the idea of dignity.